Drug monitoring detects under- and overdosing in patients receiving 5-fluorouracil-containing chemotherapy - results of a prospective, multicenter German observational study - Li, Moying; Mindt, S.; Lück, A.; Hutzschenreuter, U.; Kollendt, M.; Lathan, B.; Zöller, T.; Frank-Gleich, S.; Lorentz, C.; Lamberti, C.; Sick, C.; Zingerle, M.; et al. (ESMO open, 2023)
Introduction - Body surface area (BSA)-based dosing of 5-fluorouracil (5-FU) results in marked inter-individual variability in drug levels, whereas determination of plasma 5-FU concentration and area under the curve (AUC) is a more precise dosing method but has not been integrated into clinical routine. We conducted a multicenter, prospective study to study 5-FU AUC distributions and assess clinical factors predicting therapeutic dosing in patients receiving BSA-dosed 5-FU. - Methods - Between June 2017 and January 2018, a total of 434 patients receiving continuous, infusional BSA-dosed 5-FU from 37 sites in Germany were included. Plasma 5-FU concentration and AUC were measured in venous blood samples at steady state. The primary objective was to determine 5-FU AUC distributions in relation to the target range, which is defined as 20-30 mg × h/l. The second objective was to explore clinical parameters that correlate with achievement of 5-FU AUC target range. - Results - The primary tumor was mainly located in the gastrointestinal tract (96.3%), with colorectal cancer being the most common (71.2%) tumor entity. 5-FU was administered as monotherapy (8.1%) or as part of FOLFOX (33.2%), FOLFIRI (26.3%), or other regimens (12.4%). Treatment setting was adjuvant (31.3%) or metastatic (64.5%). The median AUC was 16 mg × h/l. Only 20.3% of patients received 5-FU treatment within the target range, whereas the majority of patients (60.6%) were underdosed and 19.1% of patients were overdosed. In the univariate logistic regression, treatment setting was the only clinical parameter that significantly correlated with achievement of the target range. Patients treated in the metastatic setting had a 2.1 (95% confidence interval 1.186-3.776, P = 0.011) higher odds to reach the target range compared with patients treated in the adjuvant setting. - Conclusions - The majority of patients received suboptimal doses of 5-FU using BSA dosing. Therapeutic drug monitoring of 5-FU is an option for optimized individualized cancer therapy and should be integrated into the clinical practice.
Online verfügbar: 23. März 2023
Gesehen am 15.08.2023